The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/bjs.10839
|View full text |Cite
|
Sign up to set email alerts
|

Two-year results of the randomized clinical trial DILALA comparing laparoscopic lavage with resection as treatment for perforated diverticulitis

Abstract: BackgroundTraditionally, perforated diverticulitis with purulent peritonitis was treated with resection and colostomy (Hartmann's procedure), with inherent complications and risk of a permanent stoma. The DILALA (DIverticulitis – LAparoscopic LAvage versus resection (Hartmann's procedure) for acute diverticulitis with peritonitis) and other randomized trials found laparoscopic lavage to be a feasible and safe alternative. The medium‐term follow‐up results of DILALA are reported here.MethodsPatients were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
10

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 27 publications
1
60
0
10
Order By: Relevance
“…144 The diverticulitis-laparoscopic lavage (DILALA) trial found fewer operations and improved stoma-free survival in the lavage group, and, in contrast to the 2 previous studies, concluded that the use of lavage was feasible and safe. 145 Unfortunately, lavage has been studied only as a substitute for resection (definitive treatment) rather than as a bridge to resection (damage control) with a primary anastomosis. 146 At this time, the use of laparoscopic lavage is not recommended outside of clinical trials, given its association with persistent and recurrent abdominal sepsis.…”
Section: Surgerymentioning
confidence: 99%
“…144 The diverticulitis-laparoscopic lavage (DILALA) trial found fewer operations and improved stoma-free survival in the lavage group, and, in contrast to the 2 previous studies, concluded that the use of lavage was feasible and safe. 145 Unfortunately, lavage has been studied only as a substitute for resection (definitive treatment) rather than as a bridge to resection (damage control) with a primary anastomosis. 146 At this time, the use of laparoscopic lavage is not recommended outside of clinical trials, given its association with persistent and recurrent abdominal sepsis.…”
Section: Surgerymentioning
confidence: 99%
“…In our study, nine patients (24%) underwent sigmoidectomy during follow‐up. In previous reports on long‐term outcomes after LL, sigmoidectomy rates of 44.7% and 21% were reported . In the cohort presented by White et al .…”
Section: Discussionmentioning
confidence: 94%
“…In our cohort there was no intention to treat patients by elective sigmoidectomy unless otherwise indicated during follow-up. The sigmoidectomy rate reported at 2-year follow-up in the DILALA trial was 21% (n = 43) [13,29]. In the recently published LLO Study, the overall reoperation rate was 26% (56/212 patients) [33].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the SCANDIV (Scandinavian Diverticulitis) trial, a larger number of patients in the lavage group underwent unplanned reoperations, but the resection group needed more planned reoperations (stoma reversals). Not surprisingly, therefore, laparoscopic lavage is more cost‐effective than resection and follow‐up of the DILALA (DIverticulitis – LAparoscopic LAvage versus resection (Hartmann's procedure) for acute diverticulitis with peritonitis) trial found a 45 per cent reduced risk of undergoing one or more operations in the lavage group.…”
mentioning
confidence: 99%